Edukasi Pentingnya ASI Eksklusif dalam Meningkatkan Status Gizi Balita di Wilayah Kerja Puskesmas Lawa Kabupaten Muna Bara - Rahmi Awanda (Lembaga Pengembangan Kinerja Dosen, 2026)
Exclusive breast milk (ASI) is the best source of nutrition for infants, playing a vital role in supporting growth and improving the nutritional status of toddlers. However, mothers' knowledge regarding the importance of exclusive breastfeeding still needs to be improved. This community service activity aims to increase the knowledge of mothers of toddlers about the importance of exclusive breastfeeding in improving their nutritional status through health education. The activity was carried out on June 17, 2026, at the Lawa Community Health Center in West Muna Regency, targeting 13 mothers of toddlers. The methods used included a pre-test, counseling through interactive lectures, discussions, and questions and answers, as well as a post-test as an evaluation. The results showed an increase in participant knowledge, where the good knowledge category increased from 23.1% to 84.6%, while the poor knowledge category decreased from 46.1% to 0% after education. In addition, most participants were able to explain the benefits of exclusive breastfeeding, the relationship between breast milk and toddler nutritional status, and the appropriate timing for providing complementary foods. Health education has been proven effective in increasing maternal knowledge and is expected to support the success of exclusive breastfeeding and improve the nutritional status of toddlers.